We are given the following two equations
![\begin{gathered} 8x+4y=0\quad eq.1 \\ 7x+8y=9\quad eq.2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ympblzg3rllthu34ghv3xbc62kfnqsxifb.png)
Let us solve these equations using the substitution method.
Separate out one variable from eq. 1
![\begin{gathered} 8x+4y=0 \\ 4y=-8x \\ y=-(8x)/(4) \\ y=-2x\quad eq.1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9jns8o2hlxw6403x7ii6836egz48ummv61.png)
Now substitute this value of y into the eq.2
![\begin{gathered} 7x+8y=9 \\ 7x+8(-2x)=9 \\ 7x-16x=9 \\ -9x=9 \\ x=(9)/(-9) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1j7ugsjagoiamfz5pkhc4hk7bug6d1lmmj.png)
So, we got the value of x and we can substitute this value into eq.1 to find the value of y.
![\begin{gathered} y=-2x \\ y=-2(-1) \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yfpwdkvv3yj8xpwoz5ybtkgtlzcz2ny98d.png)
Therefore, the solution of this system of equations is
x = -1 and y = 2